2014
DOI: 10.1007/s40272-014-0096-y
|View full text |Cite
|
Sign up to set email alerts
|

Oral Morphine Weaning for Neonatal Abstinence Syndrome at Home Compared with In-Hospital: An Observational Cohort Study

Abstract: We present the first North American cohort of neonates weaned with morphine at home for neonatal abstinence syndrome (NAS). We found that more days on oral morphine resulted in fewer returns to hospital for continued withdrawal management. There was no evidence of increased effectiveness, measured by the number of returns to hospital for further NAS management with in-hospital weaning. The estimated cost savings of continued weaning upon discharge was approximately $11,000 per patient (Canadian dollars). While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 17 publications
2
36
0
Order By: Relevance
“…This finding is consistent with previous reports that a shorter length of inpatient stay may be achieved with a longer course of opioid treatment. 20 The extended treatment duration is a consequence of a less aggressive home versus inpatient weaning schedule. Still, implementation of stringent weaning guidelines at the site led to a significant, nearly 1-week reduction in treatment duration (26.3 days vs 32.9 days, P = .04).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous reports that a shorter length of inpatient stay may be achieved with a longer course of opioid treatment. 20 The extended treatment duration is a consequence of a less aggressive home versus inpatient weaning schedule. Still, implementation of stringent weaning guidelines at the site led to a significant, nearly 1-week reduction in treatment duration (26.3 days vs 32.9 days, P = .04).…”
Section: Discussionmentioning
confidence: 99%
“…The long-term implications of prolonged opioid treatment on neurocognitive development are not well understood, and appropriate safeguards and transition models must be implemented before the administration of opioid weans with limited clinical supervision. [20][21][22][23] Concerns about providing morphine or methadone to opiate-addicted parents may be unfounded because the average infant dose is reportedly ,0.2% of the average maternal dose. 21 Nevertheless, social work assessment may aid in the selection of appropriate candidate families to receive treatment in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…10–14 Some have found benefit of home management once infants are stable. 15,16 Furthermore, recent studies have also shown that standardized protocols for NAS management are associated with shorter lengths of stay and decreased hospital costs. 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…However, a combined inpatient/outpatient treatment approach can reduce the total length of stay by ~50% compared to inpatient only, but is associated with significantly longer lengths of treatment. 28,42,56 Methadone is the most commonly employed agent due to a longer half-life, though phenobarbital and morphine have been used. It should be noted that these findings are all based upon retrospective reviews and not randomized, prospective investigations.…”
Section: Outpatient Treatmentmentioning
confidence: 99%
“…Although reports of small numbers of infants suggest the practice is safe, sudden infant death attributed to bed sharing and unsafe sleep practice has been recently reported in a cohort of infants weaned at home using morphine. 56 …”
Section: Outpatient Treatmentmentioning
confidence: 99%